The Twin Transformation Butterfly - Anne-Sophie Christmann; Carlotta Crome; Valerie Graf-Drasch; Anna Maria Oberländer; Leonie Schmidt (Business & Information Systems Engineering, 2024)
Abstract Complex digitalization and sustainability challenges shape today's management agendas. To date, the dedication of Information Systems research to both challenges has not been equal in terms of effort and reward. Building capabilities to leverage the synergetic potential of digital and sustainability transformation may enhance organizational performance and imply new value creation for the common good. To uncover such synergetic potential, this work conceptualizes the “twin transformation” construct as a value-adding reinforcing interplay between digital transformation and sustainability transformation efforts that improve an organization by leveraging digital technologies to enable sustainability and to guide digital progress by leveraging sustainability. The twin transformation conceptualization is complemented with a capability framework for twin transformation drawing from dynamic capability theory. This work contributes to descriptive knowledge of the interplay between digital transformation and sustainability transformation, setting a foundation for further theorizing on twin transformation and enabling organizations to twin transform.
Keywords: 330; Twin transformation; Digital transformation; Sustainability transformation; Dynamic capabilities